Identity Capital in Serbian Youth: A Pilot Study (Engrami, 2025)
In our study comprising 522 emerging adults we have tried to determine the level of integration in adult society and the variables that contribute to this that are described in the identity capital model based on Erikson’s lifelong development theory. We have found that a highly significant percentage of variance is determined by certain personality characteristics such as self-esteem and locus of control, and by identity variables such as commitment making, identifying with commitment, exploration in breadth and exploration in depth. Negative outcome identity variables such as ruminative exploration do not have any significant influence on the model. While examining previous studies we can make a case that as the increase in age of young adults that participate in the study increases the influence of identity variables on the model.
Keywords: Identity capital; Erikson; Scale adaptation